Graduate perceptions of customer service in institutions of higher learning - Walters, Danny D. (Kansas State University, 2011)
The purpose of this basic interpretative qualitative study was to discover and understand graduates’ perceptions of customer service from their chosen college or university. How graduates perceive customer service of institutions of higher learning may induce some educational institutions to pursue continuous improvement and performance excellence. Graduates from the master’s level or higher have spent more than the average time in the educational setting compared to undergraduates or bachelor’s level students and are more likely to have greater awareness concerning the customer service attributes. These perceptions could give rise to process improvement techniques and programs that would be useful for a variety of institutions. The method used to acquire the data was interviewing individuals who had completed at least their master’s degree. The results of these interviews were analyzed by consolidating, reducing, and interpreting what the interviewees had to say and what the researcher discovered. Triangulation through reflection and field notes was utilized to ensure credibility of findings.
Keywords: Customer Service; Graduate Perceptions; Higher Learning; Performance Excellence; Adult Education (0516)